三角函数公式

导函数

  • %%(cscx)^’=-cscxcotx%%
  • %%(secx)^’=secxtanx%%
  • %%(tanx)^’=sec^2x%%
  • %%(cotx)^’=-csc^2x%%
  • %%(arcsinx)^’=1/sqrt(1-x^2)%%
  • %%(arccosx)^’=-1/sqrt(1-x^2)%%
  • %%(arctanx)^’=1/(1+x^2)%%
  • %%(arc\cotx)^’=-1/(1+x^2)%%
  • %%(tan^2x)^’=2tan{:1/x:}%%

二倍角公式

  • %%sin2x=2sinxcosx%%
  • %%cos2x=cos^2x-sin^2x=2cos^2x-1=1-2sin^2x%%

  • %%tan2x=(2tanx)/(1-tan^2x)%%
  • %%sin^2x=(1-cos2x)/2%%
  • %%cos^2x=(1+cos2x)/2%%

三角函数不等式与恒等式

  • 若 %%x in (0,pi/2)%%, 则 %%sinx<x<tanx%%
  • 若 %%x in (0,pi/2)%%, 则 %%1<sinx+cosx<=sqrt(2)%%
  • %%|sinx|+|cosx|>=1%%
  • %%arctanx+arctan(1/x)=pi/2 (x>0)%%
  • %%arc tanx+arc cotx=pi/2%%
  • %%arc sinx+arc cosx=pi/2 (|x|<=1)%%

同角三角函数的基本关系式

  • %%cscx=1/sinx%%
  • %%secx=1/cosx%%
  • %%tanx=sinx/cosx%%
  • %%sin^2x+cos^2x=1%%
  • %%tanx * cotx=1%%
  • %%1+tan^2x=sec^2x%%
  • %%1+cot^2x=csc^2x%%
  • %%tan^2x=sec^2x-1%%

诱导公式

  • %%sin(pi/2-x)=cosx,cos(pi/2-x)=sinx%%
  • %%sin(pi/2+x)=cosx,cos(pi/2+x)=-sinx%%

三倍角公式

  • %%sin3x=3sinx-4sin^3x=4sinxsin(pi/3-x)sin(pi/3+x)%%

  • %%cos3x=4cos^3x-3cosx=4cosxcos(pi/3-x)sin(pi/3+x)%%

  • %%tan3x=(3tanx-tan^3x)/(1-3tan^2x)=tanxtan(pi/3-x)tan(pi/3+x)%%

半角公式

  • %%sin{:x/2:}=sqrt((1-cosx)/2)%%
  • %%cos{:x/2:}=sqrt((1+cosx)/2)%%
  • %%tan{:x/2:}=sqrt((1-cosx)/(1+cosx))=(1-cosx)/sinx=sinx/(1+cosx)%%

  • %%1+sinx=(sin{:x/2:}+cos{:x/2:})^2%%
  • %%1-sinx=(sin{:x/2:}-cos{:x/2:})^2%%

和差化积

  • %%sinx+siny=2sin{:(x+y)/2:}cos{:(x-y)/2:}%%
  • %%sinx-siny=2cos{:(x+y)/2:}sin{:(x-y)/2:}%%
  • %%cosx+cosy=2cos{:(x+y)/2:}cos{:(x-y)/2:}%%
  • %%cosx-cosy=-2sin{:(x+y)/2:}sin{:(x-y)/2:}%%
  • %%tanx+tany=sin(x+y)/(cosxcosy)%%

积化和差

  • %%sinxsiny=-1/2[cos(x+y)-cos(x-y)]%%
  • %%cosxcosy=1/2[cos(x+y)+cos(x-y)]%%
  • %%sinxcosy=1/2[sin(x+y)+sin(x-y)]%%
  • %%cosxsiny=1/2[sin(x+y)-sin(x-y)]%%

万能公式

  • %%sinx=(2tan{:x/2:})/(1+tan^2{:x/2:})%%
  • %%cosx=(1-tan^2{:x/2:})/(1+tan^2{:x/2:})%%
  • %%tanx=(2tan{:x/2:})/(1-tan^2{:x/2:})%%

和角与差角公式

  • %%sin(x+-y)=sinx cosy+-cosx siny%%
  • %%cos(x+-y)=cosxcosy∓sinxsiny%%
  • %%tan(x+-y)=(tanx+-tany)/(1∓tanxtany)%%
  • %%cot(x+-y)=(cotxcoty∓1)/(coty+-cotx)%%
  • %%sin(x+y)sin(x-y)=sin^2x-sin^2y%%
  • %%cos(x+y)cos(x-y)=cos^2x-sin^2y%%
  • %%asinx+bcosx=sqrt(a^2+b^2)(sinx*a/sqrt(a^2+b^2)+cosx*b/sqrt(a^2+b^2))=sqrt(a^2+b^2)sin(x+phi),tanphi=b/a%%

  • %%asinx-bcosx=sqrt(a^2+b^2)(sinx*a/sqrt(a^2+b^2)-cosx*b/sqrt(a^2+b^2))=sqrt(a^2+b^2)sin(x-phi),tanphi=b/a%%